Enhancing English Vocabulary Through Mobile Legends: Insights from EFL Students - Sinaga, Yanti Kristina; Sipayung, Rohdearni Wati; Herman, Herman; Nainggolan, Anggi Maria; Ngongo, Magdalena; Fatmawati, Endang; Thao, Nguyen Van (Pandawan, 2025)
This research aimed to explore students perceptions of playing Mobile Legends: Bang-Bang (MLBB) as a means to improve their English vocabulary. The students had limited English vocabulary, which negatively affected their learning, especially in understanding imperative statements. This study used a qualitative approach based on the Miles and Huberman analytical framework. Data were collected from 150 ninth-grade students at Junior High School 10 Pematangsiantar through closed questionnaires focusing on content vocabulary and perceptions (auditory and visual). The responses were analyzed using a 5-point Likert scale, input into Ms. Excel, and then tabulated. The results were then described descriptively in paragraph form. The findings revealed that a significant number of students reported positive outcomes regarding the influence of MLBB on vocabulary improvement. Specifically, 69.21% of students responded positively, with 13.88% strongly agreeing and 55.33% agreeing. Neutral responses accounted for 19.38%, while negative feedback totaled 11.42%, including 8.88% disagreeing and 2.54% strongly disagreeing. Regarding auditory and visual perception, 74.34% gave favorable responses, 16.7% remained neutral, and 9.6% responded negatively. The researcher concluded that most students at Junior High School 10 Pematangsiantar considered MLBB to be a beneficial alternative for improving their English vocabulary, with a significant majority expressing positive opinions about the game.